USING ACADEMIC CONTROL BELIEFS TO PREDICT COLLEGE STUDENTS’ SELF-REGULATED LEARNING BEHAVIORS - Yang, Yang (My University, 2015)
As more and more students enter colleges in the United States, the number of students who are academically underperformed for college-level work is increasing [9]. One factor that influences students’ learning is the typical behaviors students exhibit when they are studying [3], [19]. This study examined the importance of various learning behaviors carried out by college students. Furthermore, the study examined whether and to what degree one psychological attribute, locus of control, can predict students’ learning behaviors.
Citation: Yang, Y. (2015). Using academic control beliefs to predict college students' self-regulated learning behaviors. Proceedings of the International Society for Engineering Research and Development conference, Shanghai, China. ISBN: 9789385832604
Keywords: Locus Of Control Beliefs; Self-Regulated Learning Behaviors